Material Justice in Max Weber - Mendes-Quezado Ferrández, Annemaxmille (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This paper aims to present and discuss the idea of material justice developed by Max Weber throughout his work Economy and Society, and its effects in justice in contemporary societies. It aims to make a critic of the basic premises of legal positivism in the light of the Weberian thought and draw attention to the ethical character of the law, and the need to enforce the values and constitutional guarantees recognized as important for the society and the political goals of democratic rule of law. The challenge is to overcome the difficulties impeding the effectiveness of democratic rule of law and the conditions that determine the influence of politics and economy in law to find the best way to ensure that laws are properly established.
Keywords: Material justice; Max Weber; legal positivism; policy; economy